Value Oriented Organizations with Value Neutral Hierarchies - Manuel Echeverría (Lund University, School of Economics and Management, Department of Economics, 2012)
This paper gives a game-theoretical treatment of the institutional homogenization of value-oriented firms. It explains why intrinsically motivated, value-oriented firms like non-profits may become similar to for-profit firms in terms of organization and norms. It highlights and explains the pairs: value-oriented and flat organizations in contrast to value-neutral managers and hierarchical organizations. We consider a major donor like the government who delegates a project to an organization without endowments under asymmetric information. The non-profit is able to adapt its organization by establishing a hierarchy with an intrinsically motivated manager. The donor can in turn react by employing institutions in order to cope with information asymmetries regarding the mission of the organization and the unverifiable values of the manager. Two main cases are examined, one without competition and a competitive case. The equilibrium in the first case is a flat organization or alternatively highly altruistic hierarchy. The second competitive case is characterized by a value neutral hierarchy.
Keywords: L30; L31; L33; M12; M14; 330; Institutional change; Governance; Nonprofit; Hierarchy; Culture